Teachers’ Perception of the Students’ Readiness for Self- regulated Learning during the COVID-19 Pandemic - Nepal, Karuna; KC, Saban Kumar (Journal of NELTA, 2020)
COVID - 19 pandemic has detrimental impacts on the educational sector along with many other areas of human life. Virtual learning, though not a new topic, has occupied huge space in current pedagogical discourse. However, it has been criticized for exacerbating inequalities between well-resourced and under-resourced people, institutions and geographical location. In this scenario, we propose self-regulated learning as a viable solution to avert the learning gap during possible crises in the future. In this article, we explored how empowered are the learners for carrying out self-regulated learning. This qualitative study in which data were elicited through three focus group discussions with 15 ELT teachers revealed that the students having a lack of sufficient knowledge and skill for continuing learning in the absence of a teacher, indicated to the possible discontinuation of learning during the school closure circumstanced by COVID- 19 pandemic.